Diarrhea associated with afatinib: an oral ErbB family blocker. Issue 6 (June 2013) - Yang, James Chih-Hsin; Reguart, Noemi; Barinoff, Jana; Köhler, Jens; Uttenreuther-Fischer, Martina; Stammberger, Uz; O'Brien, Dennis; Wolf, Jürgen; Cohen, Ezra EW
Gastrointestinal (GI) adverse events (AEs) are frequently observed in patients receiving EGF receptor (EGFR; also known as HER1 or ErbB1) tyrosine kinase inhibitor therapy. GI AEs are among the most common and most impactful on a patient's quality of life. Severe diarrhea can result in fluid and electrolyte losses, leading to dehydration, electrolyte imbalances and renal insufficiency. Afatinib is an irreversible, oral, ErbB family blocker, inhibiting EGFR (ErbB1), HER2 (ErbB2) and ErbB4 receptor kinases. It also inhibits transphosphorylation of ErbB3. Similar to reversible tyrosine kinase inhibitors of EGFR, GI AEs – in particular, diarrhea – have frequently been observed in afatinib-treated patients. This article summarizes current data on afatinib-associated diarrhea and provides strategies for its management. Patient education, early identification, timely management and ongoing assessment will help to prevent aggravation, afatinib dose reductions or therapy discontinuation, encouraging patient compliance and allowing patients to obtain the maximum therapeutic benefit from this agent.